norCBD disruption affects the H2-type six secretion system and multiple virulence factors in Pseudomonas aeruginosa - Haque, Md Mahamudul; Badr, Sara; Duan, Kangmin (Frontiers in Microbiology, 2025)
The type six secretion system (T6SS) is a macromolecular weapon used by many Gram-negative bacteria. The T6SS functions as a needle injection system that delivers effector proteins directly into neighboring bacterial cells, thereby affecting their gene expression and physiological processes. Pseudomonas aeruginosa possesses at least three distinct T6SSs, designated as H1-, H2-, and H3-T6SS. Although extensive studies have been carried out on these T6SS systems in recent years, the regulatory mechanisms of T6SS remain incomplete. Here, we report the identification of norCBD as an operon that modulates the transcriptional activity of H2-T6SS. Both transposon insertion at norCBD and the deletion of the norCBD genes significantly reduced the CTX-H2-T6SS reporter activity. The norCBD operon encodes nitric oxide reductase (NorCBD), which reduces nitric oxide (NO) to nitrous oxide (N2O), a crucial step in reducing the toxic level of intracellular NO and facilitating anaerobic respiration. As the transcriptional regulator Dnr activates H2-type VI secretion system (H2-T6SS) in response to NO, experiments were carried out to examine whether norCBD deletion caused intracellular NO accumulation, which in turn disrupted Dnr-dependent regulation of H2-T6SS and virulence factors. The NO levels and Dnr-regulated gene expression were measured, and several virulence-related phenotypes were examined. The effects of NO donor sodium nitroprusside (SNP) and NO scavenger carboxy-phenyl-tetramethylimidazolineoxyl (CPTIO) were also tested. The data obtained indicate that deletion of norCBD led to intracellular NO accumulation, reduced H2-T6SS expression, and affected motility, pyocyanin production, and biofilm formation. Complementation of norCBD on a plasmid in the deletion mutant was able to restore H2-T6SS expression and the examined phenotypes to the wild-type levels. Treatment with CPTIO also restored H2-T6SS expression in the PAO1(ΔnorCBD). These results indicate that NorCBD plays a critical role in maintaining NO homeostasis that is necessary for effective Dnr-mediated gene regulation and multiple virulence-related traits, highlighting the importance of redox balance in coordinating respiration and pathogenesis in P. aeruginosa.